Regularity of geometric quadratic stochastic operator generated by 2-partition of infinite points - Karim, Siti Nurlaili; Hamzah, Nur Zatul Akmar; Ganikhodjaev, Nasir (Penerbit UTM Press, 2020)
In this research, we construct a class of quadratic stochastic operator called Geometric quadratic stochastic operator generated by arbitrary 2-partition of infinite points on a countable state space , where . We also study the limiting behavior of such operator by proving the existence of the limit of the sequence through the convergence of the trajectory to a unique fixed point. It is established that such operator is a regular transformation.